Er:YAG Laser for Brackets Bonding: A SEM Study after Debonding. (22nd October 2014) - Ierardo, G.; Di Carlo, G.; Petrillo, F.; Luzzi, V.; Vozza, I.; Migliau, G.; Kornblit, R.; Rocca, J. P.; Polimeni, A.
Abstract : Background . The introduction of Er:YAG laser in dentistry for ablation of hard tissues advocated an alternative method of enamel etching for orthodontics purpose. Materials and Methods . 55 extracted human third molars were inserted in acrylic resin blocks and divided into five groups of 11 teeth. Group 1 was treated with 37% orthophosphoric acid for 30 seconds. Group 2 was treated with laser irradiation (Er:YAG Fidelius III, Fotona, Slovenia) at 80 mJ and 4 Hz. Group 3 underwent laser treatment (80 mJ, 4 Hz), followed by 37% orthophosphoric acid for 30 seconds. The teeth in Group 4 were treated with laser at 40 mJ and 10 Hz. The teeth in Group 5 were treated with laser (40 mJ, 10 Hz), followed by 37% orthophosphoric acid for 30 seconds. The adhesive remnant index was determined after debonding. Results . Kruskas-Wallis test showed that location parameters (median and mean) are significantly different between Groups 2 and 4 when compared with control group; on the contrary no significant difference was detected between Groups 3 and 5 with the controls. Conclusion . The use of Er:YAG laser alone, as in Groups 2 and 4, showed no significant advantages over phosphoric acid in the bonding procedure for orthodontics brackets.